Economic Dimensions of Tono and Vea Inland Fisheries of the Upper East Region of Ghana (Journal of Science and Technology, 2016)
This research sought to explore and understand the contribution of the fishery subsector of the Tono and Vea irrigation projects within the context of employment, income and revenue generations. The central argument of the study is that the continuous investment and appropriation of the fishery resources is being guided by an access regime in operation. Adopting a case study design, it triangulated both secondary and primary sources of data for effective analysis. Through random and systematic sampling, 192 fishermen and fishmongers were selected for the study. Structured and semi-structured interview techniques were used to solicit views from primary sources and complemented with relevant secondary documents from the organisations investigated (ICOUR and MoFA). Empirical results revealed that the access regime to the fishery was significantly open access and growth in the profit variable of the fishery was more induced by tonnes of fish catch than price. The fishery can play its proper role of improving upon direct and ancillary fishery income and employment when the ‘livelihood approach’ is used to value the river fisheries and the ecosystem for sustainable rural livelihoods.